Adverse effects of anxiety on attentional control differ as a function of experience: A simulated driving study - Gotardi, Gisele C. [UNESP]; Polastri, Paula F. [UNESP]; Schor, Paulo; Oudejans, Raoul R. D.; van der Kamp, John; Savelsbergh, Geert J. P.; Navarro, Martina; Rodrigues, Sergio T. [UNESP] (Elsevier B.V., 2019)
This study tested whether adverse effects of state anxiety on attention and performance may be modulated by experience. Sixteen experienced and eleven inexperienced drivers drove in a simulator under low- and high-stress conditions. Anxiety was manipulated by competition, the presence of an evaluator, external video camera, and traffic noise. Most drivers showed greater anxiety scores and higher mean heart rates following manipulation. In both groups increased state anxiety decreased car speed control and caused more collisions, accompanied by fewer fixations of longer duration towards the driving lane across a horizontally narrower region. Inexperienced drivers increased the number of short fixations towards cars, while experienced drivers increased the number of short fixations on the speedometer. Although anxiety impairs processing efficiency and performance effectiveness for both groups, attentional changes differ as a function of experience. Inexperienced drivers tended to shift attention to threatening stimuli, while experienced drives were more likely to consciously monitor task goal.
Keywords: Anxiety; Driving experience; Gaze; Attentional control theory